Genetic compendium of 1511 human brains available through the UK Medical Research Council Brain Banks Network Resource - Keogh, Michael J.; Wei, Wei; Wilson, Ian; Coxhead, Jon; Ryan, Sarah; Rollinson, Sara; Griffin, Helen; Kurzawa-Akanbi, Marzena; Santibanez-Koref, Mauro; Talbot, Kevin; Turner, Martin R.; McKenzie, Chris-Anne; et al. (Genome Research, 2017)
Given the central role of genetic factors in the pathogenesis of common neurodegenerative disorders, it is critical that mechanistic studies in human tissue are interpreted in a genetically enlightened context. To address this, we performed exome sequencing and copy number variant analysis on 1511 frozen human brains with a diagnosis of Alzheimer's disease (AD, n = 289), frontotemporal dementia/amyotrophic lateral sclerosis (FTD/ALS, n = 252), Creutzfeldt-Jakob disease (CJD, n = 239), Parkinson's disease (PD, n = 39), dementia with Lewy bodies (DLB, n = 58), other neurodegenerative, vascular, or neurogenetic disorders (n = 266), and controls with no significant neuropathology (n = 368). Genomic DNA was extracted from brain tissue in all cases before exome sequencing (Illumina Nextera 62 Mb capture) with variants called by FreeBayes; copy number variant (CNV) analysis (Illumina HumanOmniExpress-12 BeadChip); C9orf72 repeat expansion detection; and APOE genotyping. Established or likely pathogenic heterozygous, compound heterozygous, or homozygous variants, together with the C9orf72 hexanucleotide repeat expansions and a copy number gain of APP, were found in 61 brains. In addition to known risk alleles in 349 brains (23.9% of 1461 undergoing exome sequencing), we saw an association between rare variants in GRN and DLB. Rare CNVs were found in <1.5% of brains, including copy number gains of PRPH that were overrepresented in AD. Clinical, pathological, and genetic data are available, enabling the retrieval of specific frozen brains through the UK Medical Research Council Brain Banks Network. This allows direct access to pathological and control human brain tissue based on an individual's genetic architecture, thus enabling the functional validation of known genetic risk factors and potentially pathogenic alleles identified in future studies.